Entrepreneurship among People with Disabilities in Unstable Macroenvironment Conditions - Andrzej Koza; Adriana Politaj (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu)
Aim: The study attempted to characterise and identify the behaviour of people with disabilities operating as self-employed entrepreneurs in the period of dynamic changes in the macroenvironment related to the outbreak of the COVID-19 pandemic and the war in Ukraine.